The Gold Rush Letters of E. Allen Grosh and Hosea B. Grosh - Grosh, E. Allen, 1824-1857 (Book collections on Project MUSE., 2012)
The Groshes' letters are rich in color and important historical details. Generously annotated and with an introduction that provides a context for the brothers' career and the setting in which they tried to make their fortune, these documents depict the often harsh realities of Gold Rush life and society.